THE IMPLEMENTATION OF WOMEN’S SAVING AND LOAN OF PNPM MPD IN MLATI DISTRICT - SLEMAN VIEWED FROM THE PERSPECTIVE OF ISLAMIC ECONOMICS” - Sinta Ayu Purnamasari; Achmad Fachrudin; Anton Wijaya (FEB Universitas Sultan Ageng Tirtayasa, 2019)
Conducted in Mlati District-Sleman, Yogyakrta, this study aims to investigate the implementation of women's credit program (SPP) PNPM MPD in the area to determine the level of contribution of such program in community empowerment program, and to review the implementation from the perspective of Islamic economic. This study is categorized as a qualitative research, with primary and secondary data sources. The informant chosen was chairman of the UPK (Activity Management Unit) of SPP PNPM MPD in Mlati districts and 6 people from each SPP group leaders. The data collection techniques used were observation, interview, documentation, and literature. Meanwhile, the data analysis methods used were data reduction, data display, and conclusion or verification.From here, then Islamic economic offers qardhulhasanthat is combined with sodaqoh by considering the prohibition of riba(usury) and uncombined two contract within a contract, and an unspecified charity nominal amount. Based on the findings, this study suggests 1) the administrator of PNPM MPd to restore the original purpose of the program (holding the funds for the poor communities) and providing economic values of Islam that is acceptable to all religion. Next, 2) the verification team should verify the existing team as a team that prioritize the poor. 3) for government, they should position themselves equally as leader and servant for the community. The last, 4) for scholars and preachers, they should realize that they have a responsibility to provide Islamic Economic education for the community.